Effect of nitroxyl on human platelets function - Bermejo, Emilse; Sáenz, Daniel A.; Alberto, Fabiana; Rosenstein, Ruth E.; Bari, Sara E.; Lazzari, María A. (Thrombosis and Haemostasis, 2005)
There is a growing body of evidence on the role of nitric oxide (NO) in human platelet physiology regulation. Recently, interest has developed in the functional role of an alternative redox form of NO, namely nitroxyl (HNO/NO-), because it is formed by a number of diverse biochemical reactions. The aim of the present study was to comparatively analyze the effect of HNO and NO on several functional parameters of human platelets. For this purpose, sodium trioxodinitrate (Angeli’s salt, AS) and sodium nitroprusside (SNP) were used as HNO and NO releasers, respectively. Both AS and SNP significantly inhibited platelet aggregation and ATP release induced by different agonists and adrenaline. AS or SNP did not modify the expression of platelet glycoproteins (Ib, IIb-IIIa, Ia-IIa, IV), whereas they substantially decreased the levels of CD62P, CD63 and of PAC-1 (a platelet activated glycoprotein IIb/IIIa epitope) after the stimulation with ADP. AS and SNP significantly increased cGMP accumulation in a 1H-[1,2,4]oxadiazolo [4,3-a] quinoxalin-1-one (ODQ)-sensitive manner. However, while L-cysteine reduced the effect of AS, it increased the effect of SNP on this parameter. Accordingly, a differential effect of L-cysteine was observed on the antiaggregatory effect of both compounds. In summary, these results indicate that HNO is an effective inhibitor of human platelet aggregation.
Keywords: Nitroxyl; nitric oxide; platelet physiology